2009
DOI: 10.1186/1471-2172-10-32
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of humoral immunoreactivity to different wheat cultivars gliadin are present in patients with celiac disease and in patients with multiple myeloma

Abstract: Background: Immunity to food antigens (gliadin, cow's milk proteins) is in the centre of the attention of modern medicine focused on the prevention of diseases, prevention which is based on the use of appropriate restriction diet. Detection of the enhanced levels of the immune reactions to antigen(s) present in food is from this point of view of great importance because there are reports that some of health disturbances, like celiac disease (CD) and some premalignant conditions, like monoclonal gammopathy of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…This confirms observations made by others with in vitro systems: durum and emmer had less adverse effects on intestinal mucosa than bread wheat (Aurichio et al, 1982;Pogna et al, 2008). With ELISA R5, Konic-Ristic et al (2009) have also reported that durum wheat contains less coeliac-active epitopes than bread wheat.…”
Section: Relative Gluten Toxicity Of Wheat Typessupporting
confidence: 89%
See 1 more Smart Citation
“…This confirms observations made by others with in vitro systems: durum and emmer had less adverse effects on intestinal mucosa than bread wheat (Aurichio et al, 1982;Pogna et al, 2008). With ELISA R5, Konic-Ristic et al (2009) have also reported that durum wheat contains less coeliac-active epitopes than bread wheat.…”
Section: Relative Gluten Toxicity Of Wheat Typessupporting
confidence: 89%
“…With ELISA R5, Konic‐Ristic et al . () have also reported that durum wheat contains less coeliac‐active epitopes than bread wheat.…”
Section: Discussionmentioning
confidence: 97%
“…However, a recent paper demonstrated that common wheat, rye, and barley cultivars varied in this ratio, and the gluten content will be overestimated using the general conversion factor (WIESER & KOEHLER, 2009). Many studies have focused on the diversity of the celiac-toxic protein profi le of cereals, and have shown that there are differences in the immunogenic prolamin content not only among wheat, barley, and oat species but within cultivars, too (KONIC-RISTIC et al, 2009;COMINO et al, 2011COMINO et al, , 2012PRANDI et al, 2012). This diversity relates to different expression patterns of storage proteins, which is primarily determined genetically, but it is also infl uenced by environmental factors, such as soil composition, weather, infections, heat or cold shock (DUPONT & ALTENBACH, 2003;WIESER et al, 2004).…”
mentioning
confidence: 99%
“…The ELISA assay is based on a monoclonal antibody R5, which recognizes epitopes of amino acid sequences QQPFP, QQQFP, LQPFP, and QLPFP in wheat gliadins and corresponding proteins from barley (hordeins) and rye (secalins) (Kahlenberg et al, 2006;Konic-Ristic et al, 2009;Van Eckert et al, 2010). Although R5 antibody is declared to have no cross-reactivity with oat proteins, avenins may contain QQQPF sequences and they can also react properly with R5 antibody (Comino et al, 2011;Ellis et al, 1998;Osman et al, 2001).…”
Section: Resultsmentioning
confidence: 99%